2020
DOI: 10.1007/s42452-020-03589-y
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemical evaluation and mechanisms controlling groundwater in different geologic environments, Western Sokoto Basin, Northwestern Nigeria

Abstract: The hydrogeochemistry of aquifers in the western Sokoto basin was assessed. The objective of this study is to identify the impact of geological variability on groundwater hydrochemistry and the mechanisms controlling the hydrochemistry of aquifers. Univariate statistics (several samples ANOVA), Pearson's (r), and multivariate statistics-hierarchical cluster analysis (HCA) and Factor analysis (FA) were used to interpret the hydrochemistry of aquifers. Subsequently, geochemical modeling was applied to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 95 publications
(116 reference statements)
0
9
0
Order By: Relevance
“…The authors also investigated the groundwater recharge in parts of Sokoto basin in 2006. Other similar studies were conducted by Hamidu (2017), Wali et al (2020). Kogbe (1978) investigated the geochemistry of the ferruginized deposits of the Sokoto basin by measuring the concentrations of the Fe, Mn, Ni, Co, Cr, Cu, V and Ti.…”
Section: Introductionmentioning
confidence: 87%
“…The authors also investigated the groundwater recharge in parts of Sokoto basin in 2006. Other similar studies were conducted by Hamidu (2017), Wali et al (2020). Kogbe (1978) investigated the geochemistry of the ferruginized deposits of the Sokoto basin by measuring the concentrations of the Fe, Mn, Ni, Co, Cr, Cu, V and Ti.…”
Section: Introductionmentioning
confidence: 87%
“…Bacteria decompose these organic constituents using DO, consequently reducing the DO present for aquatic organisms. Chemical oxygen demand does not discriminate between biologically available and inert organic matter, and it is a measure of the total quantity of oxygen required to oxidize all organic material into carbon dioxide and water [116][117][118][119]. The COD values are always greater than BOD values, but COD measurements can be made in a few hours while BOD measurements take five days.…”
Section: Physical Chemistrymentioning
confidence: 99%
“…Chemical essentials including Ca, Mg, Cu, Cd, B, Al, K, PO4, SO4 As, and Cl, for instance, are primarily derived from rocks. Nonetheless, elements like NO3 and SO4 are derived mainly from anthropogenic sources [118,119]. Understanding the derivation and absorption level of these chemical elements in groundwater is needed for effective groundwater management.…”
Section: Cation Chemistrymentioning
confidence: 99%
“…Hydrochemical facies classification and groundwater quality studies in eastern Niger Delta, by Amadi, et al [95], showed that Hg ranged from 0.002 to 0.004 mg/l with an average value of 0.003 mg/l. Similarly, heavy metal determination and assessment in a petroleum impacted river in Nigeria's Niger Delta region by Owamah [25] revealed an average value of less than 0.35 mg/l Hg. People who drink water containing Hg above the maximum permissible level for extended periods could experience kidney damage.…”
Section: A Physical Chemistrymentioning
confidence: 99%